Perfluorinated Chemicals as Emerging Environmental Threats to Kidney Health: A Scoping Review - Stanifer, John W; Stapleton, Heather M; Souma, Tomokazu; Wittmer, Ashley; Zhao, Xinlu; Boulware, L Ebony (Clinical journal of the American Society of Nephrology, 2018)
Per- and polyfluoroalkyl substances (PFASs) are a large group of manufactured nonbiodegradable compounds. Despite increasing awareness as global pollutants, the impact of PFAS exposure on human health is not well understood, and there are growing concerns for adverse effects on kidney function. Therefore, we conducted a scoping review to summarize and identify gaps in the understanding between PFAS exposure and kidney health. We systematically searched PubMed, EMBASE, EBSCO Global Health, World Health Organization Global Index, and Web of Science for studies published from 1990 to 2018. We included studies on the epidemiology, pharmacokinetics, or toxicology of PFAS exposure and kidney-related health, including clinical, histologic, molecular, and metabolic outcomes related to kidney disease, or outcomes related to the pharmacokinetic role of the kidneys. We identified 74 studies, including 21 epidemiologic, 13 pharmacokinetic, and 40 toxicological studies. Three population-based epidemiologic studies demonstrated associations between PFAS exposure and lower kidney function. Along with toxicology studies ( =10) showing tubular histologic and cellular changes from PFAS exposure, pharmacokinetic studies ( =5) demonstrated the kidneys were major routes of elimination, with active proximal tubule transport. In several studies ( =17), PFAS exposure altered several pathways linked to kidney disease, including oxidative stress pathways, peroxisome proliferators-activated receptor pathways, NF-E2-related factor 2 pathways, partial epithelial mesenchymal transition, and enhanced endothelial permeability through actin filament modeling. A growing body of evidence portends PFASs are emerging environmental threats to kidney health; yet several important gaps in our understanding still exist.